Comparison Between the Clinical Effect of Percutaneous Kyphoplasty for Osteoporosis Vertebral Compression Fracture Patient with or Without Sarcopenia: A Retrospective Cohort Study - Peng Y; Wu X; Ma X; Xu D; Wang Y; Xia D (International Journal of General Medicine, 2023)
Yujie Peng,1 Xiaochuan Wu,1 Xinyu Ma,2 Dingli Xu,3 Yang Wang,4 Dongdong Xia1 1Orthopeadic Department, The First Affiliated Hospital of Ningbo University, Ningbo, People’s Republic of China; 2Emergency Department, The Affiliated Lihuili Hospital of Ningbo University, Ningbo, People’s Republic of China; 3Clinical Department, Health Science Center, Ningbo University Zhejiang, Ningbo, People’s Republic of China; 4Orthopeadic Department, Ningbo No.6 Hospital, Ningbo, Zhejiang, People’s Republic of ChinaCorrespondence: Dongdong Xia, Email gukeyisheng0525@163.comBackground: Sarcopenia and osteoporosis vertebral compression fractures (OVCF) are common diseases that increase with age. This study aimed to investigate the effects of sarcopenia on OVCF patients after percutaneous kyphoplasty (PKP).Methods: Data of 101 patients who were treated with single-level PKP between January 2021 and March 2022 at Ningbo No.6 Hospital were enrolled. Forty-five OVCF patients with sarcopenia who met our inclusion criteria were included in the Sarcopenia-PKP group (SPKP group), and 56 patients in the Normal-PKP group (NPKP group). All clinical and radiological data were collected from medical records. Baseline characteristics, operation-related parameters (operation time, time to ambulation, hospital stay, surgery segment), clinical outcomes (visual analog score [VAS], Oswestry Disability Index [ODI], Japanese Orthopaedic Association Scores [JOA] of lumber), radiological outcomes (vertebral anterior height rate and local kyphosis angle), Macnab score, and complications were evaluated and compared.Results: There were no significant differences in age, sex, surgical segment preoperative VAS score, ODI, or JOA between the two groups (P > 0.05). The SPKP group had a significantly lower body mass index (BMI), bone mineral density (BMD), and smooth muscle index (SMI) than the NPKP group (P < 0.05). Significantly longer hospital stays and time to ambulation in SPKP group than NPKP group (3.7± 0.8 vs 3.4± 0.5 and 2.0± 0.8 vs 1.6± 0.5, P < 0.05). In SPKP group, significantly better clinical outcomes at 6- and 12-months follow-up were observed in NPKP group than SPKP group (P < 0.05), and NPKP group showed significantly better in vertebral anterior height rates than SPKP group after 6-month follow-up (P < 0.05). Moreover, there were significantly more cases of complications in the SPKP group (P < 0.05).Conclusion: Sarcopenia could reduce the clinical effect of percutaneous kyphoplasty, and furthermore. Related studies are needed to verify the effect of sarcopenia on OVCF patients.Keywords: sarcopenia, percutaneous kyphoplasty, osteoporosis vertebral compression fracture, clinical effect